High-performance flexible transparent conductive film and preparation method thereof
Patent Information
- Application Number
- CN202611150764.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-31
AI Technical Summary
(1)、本发明利用普通载玻片或钠钙玻璃易被高温氢氧化钾或氢氧化钠溶液腐蚀的特点,将普通载玻片或钠钙玻璃浸泡在70~90℃氢氧化钠或氢氧化钾溶液中一定时间,从而在载玻片或钠钙玻璃衬底的两面制备出多孔二氧化硅薄膜。在其中一面的多孔二氧化硅薄膜上旋涂银纳米线悬浮液制备出银纳米线薄膜,该银纳米线悬浮液以无水乙醇为溶剂,经后续烘干过程,溶剂挥发,使得银纳米线均匀分散在多孔二氧化硅薄膜上,且银纳米线之间形成网格结构。随后在银纳米线上旋涂聚偏二氟乙烯溶液,聚偏二氟乙烯溶液渗入银纳米线的网格结构中并进一步渗入多孔二氧化硅薄膜的孔结构中,干燥后,通过聚偏二氟乙烯将多孔二氧化硅薄膜、银纳米线与聚偏二氟乙烯薄膜连接为一个整体,银纳米线位于多孔二氧化硅薄膜和聚偏二氟乙烯薄膜之间且嵌在聚偏二氟乙烯薄膜中,提高了银纳米线的稳定性。同时,一部分聚偏二氟乙烯填充在多孔二氧化硅薄膜的孔结构中,从而提高了多孔二氧化硅薄膜在聚偏二氟乙烯柔性基底上的附着力,使多孔二氧化硅薄膜与聚偏二氟乙烯基底之间不易脱落分离。
Smart Images

Figure CN122658734B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible conductive film preparation technology, specifically a high-performance flexible transparent conductive film and its preparation method. Background Technology
[0002] Flexible transparent conductive films possess excellent conductivity, light transmittance, and flexibility, making them widely applicable in flexible displays, wearable devices, and flexible solar cells. Silver nanowires, due to their good conductivity and flexibility, have become a hot material for flexible transparent conductive films. However, the contact between silver nanowires and flexible substrates largely relies on van der Waals forces or electrostatic interactions, resulting in poor adhesion and stability. Furthermore, silver nanowires exhibit strong light reflection; the lower the sheet resistance, the stronger the light reflection, leading to a decrease in film transmittance. This often makes it difficult to achieve flexible transparent conductive films that simultaneously possess low sheet resistance and high transmittance.
[0003] To further optimize the light transmittance of flexible transparent conductive films containing silver nanowires, a low-refractive-index silica film is often prepared on the surface of the silver nanowires. However, due to the insulating properties of silica, the sheet resistance of the flexible transparent conductive film increases sharply. To avoid deterioration of the sheet resistance, the thickness of the silica film needs to be controlled within a limited range, which limits the improvement in light transmittance. To address this issue, some researchers have designed porous silica films. Porous silica not only has a low refractive index, but its porous nature also ensures the transport of charge carriers, thus guaranteeing low sheet resistance and high light transmittance to a certain extent. However, porous silica also has poor adhesion and is easily wiped off. Therefore, there is an urgent need to develop a flexible transparent conductive film that combines high light transmittance, low sheet resistance, high adhesion, and good stability. Summary of the Invention
[0004] To address the above technical problems, this invention provides a high-performance flexible transparent conductive film and its preparation method, so as to achieve a flexible transparent conductive film with low sheet resistance, high light transmittance and excellent stability.
[0005] This invention is specifically achieved through the following technical solution: a high-performance flexible transparent conductive film is proposed according to this invention, which consists of, from bottom to top: a porous silica film, a silver nanowire film, a polyvinylidene fluoride (PVDF) film, and a silica film. In this high-performance flexible transparent conductive film, silver nanowires are uniformly dispersed on the porous silica film, forming a mesh structure between the silver nanowires. PVDF penetrates into the mesh structure of the silver nanowires and then into the pore structure of the porous silica film through this mesh structure, thus connecting the porous silica film, the silver nanowire film, and the PVDF film into a whole. The silica film is deposited on the PVDF film by magnetron sputtering.
[0006] The aforementioned high-performance flexible transparent conductive film has silver nanowire film and silicon dioxide film with thicknesses of 30~50 nm and 60~100 nm, respectively.
[0007] The aforementioned high-performance flexible transparent conductive film has a sheet resistance of 10~20 Ω / sq and an average transmittance of 90~95% in the range of 380~780 nm.
[0008] This invention also provides a method for preparing a high-performance flexible transparent conductive film, which specifically includes the following steps: S1. Immerse a clean glass slide or soda-lime glass substrate in a high-temperature sodium hydroxide or potassium hydroxide solution for 20-60 minutes to obtain a porous silica film on the front and back sides of the substrate. S2. A silver nanowire suspension is spin-coated onto the front side of the substrate obtained in step S1 using a spin coater, while the back side of the substrate is not spin-coated. After completion, the substrate is placed in an oven to dry for 10-60 min, thereby preparing a silver nanowire film on the porous silica film on the front side of the substrate. A mesh structure is formed between the silver nanowires in the silver nanowire film. S3. Spin-coat polyvinylidene fluoride solution onto the silver nanowire film obtained in step S2 using a spin coater. After completion, place it in an oven to dry for 30-60 min to obtain a polyvinylidene fluoride film. S4. A silicon dioxide film is prepared on the polyvinylidene fluoride film obtained in step S3 by magnetron sputtering. S5. Place the sample obtained in step S4 in deionized water and sonicate for 10-30 min. During the sonication process, the porous silica film separates from the substrate, and finally a high-performance flexible transparent conductive film with polyvinylidene fluoride as the substrate is obtained.
[0009] In the aforementioned method for preparing high-performance flexible transparent conductive films, in step S1, the temperature of the sodium hydroxide or potassium hydroxide solution is 70~90℃, and its concentration is 0.8~1.2 mol / L. The glass slide or soda-lime glass substrate is pretreated in advance. The pretreatment method is as follows: the glass slide or soda-lime glass substrate is placed in acetone, anhydrous ethanol, and deionized water in sequence and ultrasonically treated for 30 min each, and then dried at 60~80℃.
[0010] In the aforementioned method for preparing high-performance flexible transparent conductive films, in step S2, the concentration of the silver nanowire suspension used for spin-coating silver nanowires is preferably 0.5~1.5 mg / mL, for example, it can be: 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL, 1.3 mg / mL, 1.4 mg / mL, or 1.5 mg / mL. The spin coater is first run at a speed of 500~800 r / min for 5 s, and then at a speed of 1500~2000 r / min for 20 s, which is one cycle. The spin coating is repeated for a total of 3~5 cycles.
[0011] In the aforementioned method for preparing high-performance flexible transparent conductive films, in step S3, the polyvinylidene fluoride solution is a transparent solution obtained by dissolving polyvinylidene fluoride in N,N-dimethylacetamide. The mass fraction of polyvinylidene fluoride in the polyvinylidene fluoride solution is 10~20%, for example, it can be: 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. The spin coater first runs at a speed of 500~800 r / min for 20 s, then runs at a speed of 1500~2000 r / min for 20 s, which is one cycle, and a total of one spin coating cycle is completed.
[0012] In the aforementioned method for preparing high-performance flexible transparent conductive films, in step S4, the sputtering gas is a mixture of argon and oxygen, with an argon to oxygen flow rate ratio of 15:1. The target material used is a silicon target, and the sputtering power is 60~100 W, for example, 60W, 70W, 80W, 90W, or 100W. The sputtering pressure is 1 Pa.
[0013] In the aforementioned method for preparing high-performance flexible transparent conductive films, in step S4, the thickness of the silicon dioxide film is 60~100 nm.
[0014] In the aforementioned method for preparing high-performance flexible transparent conductive films, step S5 involves ultrasonic treatment with a power of 180W and a frequency of 40 kHz.
[0015] The aforementioned method for preparing a high-performance flexible transparent conductive film yields a high-performance flexible transparent conductive film that, from bottom to top, consists of: a porous silica film, a silver nanowire film, a polyvinylidene fluoride (PVDF) film, and a silica film. In this high-performance flexible transparent conductive film, silver nanowires are uniformly dispersed on the porous silica film, forming a mesh structure between the silver nanowires. PVDF penetrates into the mesh structure of the silver nanowires and, through this mesh structure, into the pore structure of the porous silica film, thereby connecting the porous silica film, the silver nanowire film, and the PVDF film into a single unit.
[0016] The aforementioned method for preparing high-performance flexible transparent conductive films results in high-performance flexible transparent conductive films with a sheet resistance of 10~20 Ω / sq and an average transmittance of 90~95% within the range of 380~780 nm.
[0017] Compared with the prior art, the present invention has at least the following advantages: (1) This invention utilizes the characteristic that ordinary glass slides or soda-lime glass are easily corroded by high-temperature potassium hydroxide or sodium hydroxide solutions. Ordinary glass slides or soda-lime glass are immersed in sodium hydroxide or potassium hydroxide solutions at 70-90℃ for a certain period of time, thereby preparing porous silica films on both sides of the glass slide or soda-lime glass substrate. A silver nanowire film is then prepared by spin-coating a silver nanowire suspension onto one side of the porous silica film. This silver nanowire suspension uses anhydrous ethanol as a solvent. After a subsequent drying process, the solvent evaporates, resulting in the silver nanowires being uniformly dispersed on the porous silica film, and forming a mesh structure between the silver nanowires. Subsequently, a polyvinylidene fluoride (PVDF) solution was spin-coated onto the silver nanowires. The PVDF solution penetrated into the mesh structure of the silver nanowires and further into the pore structure of the porous silica film. After drying, the porous silica film, silver nanowires, and PVDF film were connected as a whole by the PVDF. The silver nanowires were located between and embedded in the PVDF film, improving their stability. Simultaneously, some PVDF filled the pore structure of the porous silica film, thereby enhancing the adhesion of the porous silica film to the flexible PVDF substrate and preventing detachment between the two.
[0018] (2) The high-performance flexible transparent conductive film prepared by this invention ensures its excellent conductivity through silver nanowires and its excellent light transmittance through porous silica film (the porous structure in porous silica can greatly reduce light scattering and improve the light transmittance of the conductive film), thus enabling the flexible transparent conductive film to have both low sheet resistance and high light transmittance. Polyvinylidene fluoride is infiltrated into the silver nanowire mesh structure and the porous structure of porous silica, which improves the adhesion between the silver nanowires and porous silica, solving the problem that low sheet resistance, high light transmittance and high adhesion of flexible transparent conductive film cannot be achieved at the same time.
[0019] (3) The present invention can also adjust the porosity of the porous silica film by adjusting the soaking time of the substrate in sodium hydroxide or potassium hydroxide solution, thereby achieving the adjustment of the light transmittance of the flexible transparent conductive film.
[0020] (4) The preparation method of the present invention is simple, the raw materials are readily available, and the operation is convenient. The sheet resistance of the prepared high-performance flexible transparent conductive film is as low as 10~20 Ω / sq, and the average transmittance in the range of 380~780nm can reach 90~95%. It can be widely used in flexible display, wearable device, flexible solar cell and other fields. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the structure of the high-performance flexible transparent conductive film prepared by the present invention.
[0022] Figure 2 This is a SEM image of the high-performance flexible transparent conductive film prepared in Example 1.
[0023] Figure 3 It is the transmittance of the high-performance flexible transparent conductive film prepared in Example 1 in the range of 380~780 nm.
[0024] Figure 1 In the image, 1-porous silica film, 2-silver nanowire film, 3-polyvinylidene fluoride film, and 4-silica film. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Unless otherwise specified, all conditions in the following examples were performed under conventional conditions or conditions recommended by the manufacturer. Raw materials and reagents without a specified manufacturer were all commercially available products. The silicon targets used in the examples were commercially available products, and the glass slides used were ordinary glass slides. Both sides of the glass slides or soda-lime glass were identical; for ease of description, they are referred to as the "front side" and "back side," respectively.
[0027] Example 1 S1. Immerse a clean glass slide substrate in a 1.0 mol / L potassium hydroxide solution at 90°C for 30 minutes to obtain porous silica films on both the front and back sides of the glass slide. In this step, the slides are pretreated before use. Specifically, the slides are placed in acetone, anhydrous ethanol and deionized water and ultrasonically treated for 30 min each, and then dried at 60~80℃. S2. A silver nanowire suspension is spin-coated onto the front side of the glass slide obtained in step S1 using a spin coater (the back side of the glass slide is not spin-coated). After completion, the slide is placed in an oven at 60°C and dried for 10 min. This prepares a 30 nm thick silver nanowire film on the porous silica film on the front side of the glass slide. The silver nanowires in this silver nanowire film form a mesh structure, which is beneficial for the penetration of polyvinylidene fluoride (PVDF) solution during the preparation of the polyvinylidene fluoride (PVDF) film in step S3. In this step, the concentration of the silver nanowire suspension used is 1.0 mg / mL. The silver nanowire suspension uses anhydrous ethanol as the solvent. The spin coater runs at 500 r / min for 5 s and then at 1500 r / min for 20 s. This is one cycle. A total of 4 spin coating cycles are performed in this way. S3. Polyvinylidene fluoride solution is spin-coated onto the silver nanowire film obtained in step S2 using a spin coater. After completion, the film is placed in an oven at 100°C and dried for 30 min to obtain a polyvinylidene fluoride film. In this step, the polyvinylidene fluoride solution is a transparent solution obtained by dissolving polyvinylidene fluoride in N,N-dimethylacetamide, and the mass fraction of polyvinylidene fluoride in the polyvinylidene fluoride solution is 10%. The spin coater first runs at a speed of 500 r / min for 20 s, and then runs at a speed of 2000 r / min for 20 s, which is one cycle, and a total of one spin coating cycle is completed. S4. A silicon dioxide film with a thickness of 60 nm is prepared on the polyvinylidene fluoride film obtained in step S3 by magnetron sputtering. The sputtering gas is a mixture of argon and oxygen with an argon to oxygen flow ratio of 15:1. The target material is a silicon target, the sputtering power is 80 W, and the sputtering pressure is 1 Pa. S5. Place the glass slide obtained in step S4 in deionized water and sonicate for 10 min. The ultrasonic power is 180 W and the frequency is 40 kHz. Due to the poor adhesion between the porous silica film and the glass slide, and because the porous silica film is connected to the polyvinylidene fluoride film through its pore structure, the two are tightly bonded. During the ultrasonic treatment, the porous silica film separates from the glass slide, and finally a high-performance flexible transparent conductive film with PVDF (polyvinylidene fluoride) as the flexible substrate is obtained.
[0028] Testing showed that the high-performance flexible transparent conductive film prepared in this embodiment had an average transmittance of 94.2% in the range of 380–780 nm, a sheet resistance of 19.85 Ω / sq, and a quality factor of 0.028 Ω. -1 (Quality factor = 10th power of average transmittance ÷ sheet resistance).
[0029] Figure 1 This is a schematic diagram of the structure of the high-performance flexible transparent conductive film prepared according to the present invention. From bottom to top, it consists of: a porous silica film 1, a silver nanowire film 2, a polyvinylidene fluoride (PVDF) film 3, and a silica film 4. The thicknesses of the silver nanowire film 2 and the silica film 4 are 30 nm and 60 nm, respectively. In this high-performance flexible transparent conductive film, silver nanowires are uniformly dispersed on the porous silica film 1. Since a PVDF solution is used to prepare the PVDF film 3, and a mesh structure is formed between the silver nanowires in the silver nanowire film 2, a portion of the PVDF solution penetrates into the mesh structure of the silver nanowires and then into the pore structure of the porous silica film 1. Thus, the porous silica film 1, the silver nanowire film 2, and the PVDF film 3 are connected into a whole by PVDF. The silica film 4 is deposited on the PVDF film 3 by magnetron sputtering.
[0030] The preparation method of this invention sandwiches a silver nanowire film 2 between a polyvinylidene fluoride (PVDF) film 3 and a porous silica film 1, with the silver nanowires embedded in the PVDF film 3, thereby improving the adhesion of the silver nanowires to the PVDF substrate (flexible substrate). Simultaneously, the porous silica film 1, through its porous structure, firmly bonds to the PVDF, overcoming the defect of low adhesion of the porous silica film 1 on the flexible substrate, making it less prone to detachment between the porous silica film 1 and the PVDF film 3.
[0031] Figure 2 This is a microscopic image of the high-performance flexible transparent conductive film prepared in this embodiment, where silver nanowires can be clearly seen embedded in the PVDF film.
[0032] Figure 3The figures show the transmittance variation curves of the high-performance flexible transparent conductive film prepared in this embodiment and the conductive film D1 prepared in Comparative Example 1 within the range of 380~780 nm. It can be seen that the transmittance of the high-performance flexible transparent conductive film prepared in this embodiment is much higher than that of the conductive film D1 prepared in Comparative Example 1.
[0033] Example 2 S1. Immerse a clean soda-lime glass substrate in a sodium hydroxide solution with a concentration of 1.2 mol / L at 70°C for 20 min to obtain porous silica films on both the front and back sides of the soda-lime glass. In this step, the soda-lime glass is pretreated before use. Specifically, the soda-lime glass is placed in acetone, anhydrous ethanol and deionized water for ultrasonic treatment for 30 min each, and then dried at 60~80℃. S2. A silver nanowire suspension is spin-coated onto the front side of the soda-lime glass obtained in step S1 using a spin coater (the back side of the soda-lime glass is not spin-coated). After completion, it is placed in an oven at 80°C and dried for 10 min. This prepares a silver nanowire film with a thickness of 40 nm on the porous silica film on the front side of the soda-lime glass. A mesh structure is formed between the silver nanowires in the silver nanowire film, which is beneficial to the penetration of polyvinylidene fluoride (PVDF) solution when preparing the polyvinylidene fluoride (PVDF) film in step S3. In this step, the concentration of the silver nanowire suspension used is 0.6 mg / mL. The silver nanowire suspension uses anhydrous ethanol as the solvent. The spin coater runs at 500 r / min for 5 s, then at 1500 r / min for 20 s. This is one cycle. A total of 5 spin coats are performed in this way. S3. Polyvinylidene fluoride solution is spin-coated onto the silver nanowire film obtained in step S2 using a spin coater. After completion, the film is placed in an oven at 100°C and dried for 30 min to obtain a polyvinylidene fluoride film. In this step, the polyvinylidene fluoride solution is a transparent solution obtained by dissolving polyvinylidene fluoride in N,N-dimethylacetamide, and the mass fraction of polyvinylidene fluoride in the polyvinylidene fluoride solution is 10%. The spin coater first runs at a speed of 500 r / min for 20 s, and then runs at a speed of 2000 r / min for 20 s, which is one cycle, and a total of one spin coating cycle is completed. S4. A silicon dioxide film with a thickness of 80 nm is prepared on the polyvinylidene fluoride film obtained in step S3 by magnetron sputtering. The sputtering gas is a mixture of argon and oxygen with an argon to oxygen flow rate ratio of 15:1. The target material is a silicon target, the sputtering power is 80 W, and the sputtering pressure is 1 Pa. S5. The soda-lime glass obtained in step S4 is placed in deionized water and ultrasonically treated for 10 min at an ultrasonic power of 180 W and a frequency of 40 kHz. Due to the poor adhesion between the porous silica film and the soda-lime glass, and because the porous silica film is connected to the polyvinylidene fluoride film through its pore structure, the two are tightly bonded. During the ultrasonic treatment, the porous silica film separates from the soda-lime glass, ultimately yielding a high-performance flexible transparent conductive film with PVDF (polyvinylidene fluoride) as the flexible substrate. The structure of this high-performance flexible transparent conductive film is the same as in Example 1, wherein the thicknesses of the silver nanowire film 2 and the silica film 4 are 40 nm and 80 nm, respectively.
[0034] Testing showed that the high-performance flexible transparent conductive film prepared in this embodiment had an average transmittance of 92.4% in the range of 380–780 nm, a sheet resistance of 15.73 Ω / sq, and a quality factor of 0.029 Ω. -1 .
[0035] Example 3 S1. Immerse a clean glass slide substrate in a 0.8 mol / L potassium hydroxide solution at 70°C for 60 min to obtain porous silica films on both the front and back sides of the glass slide. In this step, the slides are pretreated before use. Specifically, the slides are placed in acetone, anhydrous ethanol and deionized water and ultrasonically treated for 30 min each, and then dried at 60~80℃. S2. A silver nanowire suspension is spin-coated onto the front side of the glass slide obtained in step S1 using a spin coater (the back side of the glass slide is not spin-coated). After completion, the slide is placed in an oven at 80°C and dried for 10 min. This prepares a 50 nm thick silver nanowire film on the porous silica film on the front side of the glass slide. The silver nanowires in this silver nanowire film form a mesh structure, which is beneficial for the penetration of polyvinylidene fluoride (PVDF) solution during the preparation of the polyvinylidene fluoride (PVDF) film in step S3. In this step, the concentration of the silver nanowire suspension used is 1.5 mg / mL. The spin coater is first run at 500 r / min for 5 s, and then at 1500 r / min for 20 s. This is one cycle. A total of 3 spin coating cycles are performed in this way. S3. Polyvinylidene fluoride solution is spin-coated onto the silver nanowire film obtained in step S2 using a spin coater. After completion, the film is placed in an oven at 100°C and dried for 30 min to obtain a polyvinylidene fluoride film. In this step, the polyvinylidene fluoride solution is a transparent solution obtained by dissolving polyvinylidene fluoride in N,N-dimethylacetamide, and the mass fraction of polyvinylidene fluoride in the polyvinylidene fluoride solution is 20%. The spin coater first runs at a speed of 500 r / min for 20 s, and then runs at a speed of 2000 r / min for 20 s, which is one cycle, and a total of one spin coating cycle is completed. S4. A silicon dioxide film with a thickness of 100 nm is prepared on the polyvinylidene fluoride film obtained in step S3 by magnetron sputtering. The sputtering gas is a mixture of argon and oxygen with an argon to oxygen flow ratio of 15:1. The target material is a silicon target, the sputtering power is 100 W, and the sputtering pressure is 1 Pa. S5. The glass slide obtained in step S4 is placed in deionized water and ultrasonically treated for 10 min at an ultrasonic power of 180 W and a frequency of 40 kHz. Due to the poor adhesion between the porous silica film and the glass slide, and because the porous silica film is connected to the polyvinylidene fluoride film through its pore structure, the two are tightly bonded. During the ultrasonic treatment, the porous silica film separates from the glass slide, ultimately yielding a high-performance flexible transparent conductive film with PVDF (polyvinylidene fluoride) as the flexible substrate. The structure of this high-performance flexible transparent conductive film is the same as in Example 1, wherein the thicknesses of the silver nanowire film 2 and the silica film 4 are 50 nm and 100 nm, respectively.
[0036] Testing showed that the high-performance flexible transparent conductive film prepared in this embodiment had an average transmittance of 90.8% in the range of 380–780 nm, a sheet resistance of 10.2 Ω / sq, and a quality factor of 0.037 Ω. -1 .
[0037] Comparative Example 1 S1. Silver nanowires are spin-coated on the front side of a clean glass slide substrate (the glass slide substrate is not soaked in alkaline solution) using a spin coater (the back side of the glass slide substrate is not spin-coated). The remaining operations and parameters are the same as step S2 in Example 1. S2, the same as step S3 in Example 1; S3. Place the glass slide obtained in step S2 of this comparative example in deionized water and sonicate for 10 min. Separate the glass slide from the silver nanowires and polyvinylidene fluoride film to obtain the silver nanowire-polyvinylidene fluoride conductive film D1.
[0038] Testing showed that the conductive thin film D1 prepared in this comparative example had an average transmittance of 86.7% in the range of 380–780 nm, a sheet resistance of 14.2 Ω / sq, and a quality factor of 0.017 Ω. -1The quality factor is significantly smaller than that of the high-performance flexible transparent conductive film prepared in Example 1, indicating that the overall performance of the flexible transparent conductive film prepared in Example 1 of this invention is superior to that of the conductive film D1 in Comparative Example 1.
[0039] Comparative Example 2 S1. Silver nanowires are spin-coated on the front side of a clean soda-lime glass substrate (the soda-lime glass substrate is not soaked in alkaline solution) using a spin coater (the back side of the soda-lime glass substrate is not spin-coated). The remaining operations and parameters are the same as step S2 in Example 2. S2, the same as step S3 in Example 2; S3. The soda-lime glass obtained in step S2 of this comparative example is placed in deionized water and ultrasonically treated for 10 min. The soda-lime glass is separated from the silver nanowires and polyvinylidene fluoride film to obtain the silver nanowire-polyvinylidene fluoride conductive film D2.
[0040] Testing showed that the conductive film D2 prepared in this comparative example had an average transmittance of 84.5% in the range of 380–780 nm, a sheet resistance of 13.3 Ω / sq, and a quality factor of 0.014 Ω. -1 The quality factor is significantly smaller than that of the high-performance flexible transparent conductive film prepared in Example 2, indicating that the overall performance of the flexible transparent conductive film prepared in Example 2 is superior to that of the conductive film D2 in Comparative Example 2.
[0041] Comparative Example 3 S1. Spin-coating silver nanowires onto the front side of a clean glass slide substrate (the glass slide substrate is not soaked in alkaline solution) using a spin coater (the back side of the glass slide substrate is not spin-coated). The remaining operations and parameters are the same as step S2 in Example 3. S2, the same as step S3 in Example 3; S3. Place the glass slide obtained in step S2 of this comparative example in deionized water and sonicate for 10 min. The glass slide is separated from the silver nanowires and polyvinylidene fluoride film to obtain silver nanowire-polyvinylidene fluoride conductive film D3.
[0042] Testing showed that the conductive film D3 prepared in this comparative example had an average transmittance of 83.6% in the range of 380–780 nm, a sheet resistance of 12.8 Ω / sq, and a quality factor of 0.013 Ω. -1 The quality factor is significantly lower than that of the high-performance flexible transparent conductive film prepared in Example 3, indicating that the overall performance of the flexible transparent conductive film prepared in Example 3 is superior to that of the conductive film D3 in Comparative Example 3.
[0043] The above description is merely an embodiment of the present invention and is not intended to limit the present invention in any way. The present invention can also have other embodiments based on the above structure and function, which will not be listed hereafter. Therefore, any simple modifications, equivalent changes, and alterations made by those skilled in the art to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing a flexible transparent conductive film, characterized in that, The flexible transparent conductive film consists of, from bottom to top: a porous silica film (1), a silver nanowire film (2), a polyvinylidene fluoride (PVDF) film (3), and a silica film (4). In this flexible transparent conductive film, silver nanowires are uniformly dispersed on the porous silica film (1), forming a mesh structure between the silver nanowires. PVDF penetrates into the mesh structure of the silver nanowires and then into the pore structure of the porous silica film (1) through this mesh structure, thus connecting the porous silica film (1), the silver nanowire film (2), and the PVDF film (3) into a single unit. The silica film (4) is deposited on the PVDF film (3) by magnetron sputtering. The thicknesses of the silver nanowire film (2) and the silica film (4) are 30~50 nm and 60~100 nm, respectively. This flexible transparent conductive film is prepared according to the following method: S1. Using a glass slide or soda-lime glass as a substrate, immerse the clean substrate in a sodium hydroxide or potassium hydroxide solution at 70~90℃ and a concentration of 0.8~1.2mol / L for 20~60 min to obtain a porous silica film on the front and back sides of the substrate. S2. A silver nanowire suspension is spin-coated onto the front side of the substrate obtained in step S1 using a spin coater, while the back side of the substrate is not spin-coated. After completion, the substrate is placed in an oven to dry for 10-60 min, thereby preparing a silver nanowire film on the porous silica film on the front side of the substrate. A mesh structure is formed between the silver nanowires in the silver nanowire film. S3. A polyvinylidene fluoride (PVDF) solution is spin-coated onto the silver nanowire film obtained in step S2 using a spin coater. After completion, the film is placed in an oven and dried for 30-60 minutes to obtain a PVDF film. The PVDF solution is a transparent solution obtained by dissolving PVDF in N,N-dimethylacetamide, and the mass fraction of PVDF in the PVDF solution is 10-20%. The spin coater is run at a speed of 500-800 r / min for 20 seconds, then at a speed of 1500-2000 r / min for 20 seconds, which constitutes one cycle. One spin coating cycle is completed. S4. A silicon dioxide film is prepared on the polyvinylidene fluoride film obtained in step S3 by magnetron sputtering. S5. Place the sample obtained in step S4 in deionized water and sonicate for 10-30 min. During the sonication process, the porous silica film separates from the substrate, and finally a flexible transparent conductive film with polyvinylidene fluoride as the substrate is obtained.
2. The method for preparing the flexible transparent conductive film as described in claim 1, characterized in that, The sheet resistance of the flexible transparent conductive film is 10~20 Ω / sq, and its average transmittance in the range of 380~780 nm is 90~95%.
3. The method for preparing the flexible transparent conductive film as described in claim 1, characterized in that, In step S1, the substrate is pretreated in advance. The pretreatment method is as follows: the substrate is placed in acetone, anhydrous ethanol and deionized water for ultrasonic treatment for 30 min each, and then dried at 60~80℃.
4. The method for preparing the flexible transparent conductive film as described in claim 1, characterized in that, In step S2, the concentration of the silver nanowire suspension is 0.5~1.5 mg / mL. The spin coater is first run at a speed of 500~800 r / min for 5 s, and then at a speed of 1500~2000 r / min for 20 s. This is one cycle. The spin coating is repeated for a total of 3~5 cycles.
5. The method for preparing the flexible transparent conductive film as described in claim 1, characterized in that, In step S4, the sputtering gas is a mixture of argon and oxygen, with an argon to oxygen flow rate ratio of 15:
1. The target material used is a silicon target, the sputtering power is 80~100 W, and the sputtering pressure is 1 Pa.
Citation Information
Patent Citations
High-conductivity transparent and flexible wearable electrode and preparation method and application thereof
CN108922686A
Glass with nano-silver on surface and preparation method thereof
CN116040959A
High-transmittance electric heating shielding composite film and preparation method thereof
CN121586114A